Effectiveness of education and attitudes toward different types of deceased donor kidneys: Survey analysis of single-center experience - Nair, Sumi S.; Thorp, Andrea N.; Hanna, Wael; Johnson, Bradley K.; Smith, Byron; Iyengar, Savitha; Howe, Elizabeth A.; Mour, Girish K. (Frontiers in Public Health, 2023)
Background: We lack data on the effectiveness of education and the patient’s attitude toward different deceased donor kidney types. A prospective study was performed to evaluate patient attitudes, baseline knowledge, and effectiveness of our kidney transplant education process. We also analyzed the knowledge retention of our waitlist patients. Design: We prospectively surveyed a patient cohort using a paired analysis pre and post education with initial evaluation visit. Knowledge retention among waitlist patients was assessed with annual waitlist visit. Results: 104 patients received paired surveys to assess the baseline knowledge and effectiveness of education. 43 patients received a single survey with their annual waitlist evaluation to assess knowledge retention. Paired survey showed mixed results, with no statistically significant improvement in the kidney donor profile index domain. Significant improvement was seen in the hepatitis C virus–positive donor domain and the Public Health Service (PHS) increased-risk donor domain. For the waitlist cohort, overall knowledge retention ranged from excellent to fair, with a decline in knowledge for the PHS increased-risk donor domain. Conclusion: Our study suggests that the education intervention regarding different deceased donor kidney types is effective overall and transplant candidates retain the knowledge while waiting for transplant.